2016
DOI: 10.1021/acs.biochem.6b00173
|View full text |Cite
|
Sign up to set email alerts
|

Positioning the Intracellular Salt Potassium Glutamate in the Hofmeister Series by Chemical Unfolding Studies of NTL9

Abstract: In vitro, replacing KCl by potassium glutamate (KGlu), the E. coli cytoplasmic salt and osmolyte, stabilizes folded proteins and protein-nucleic acid complexes. To understand the chemical basis for these effects and rank Glu− in the Hofmeister anion series for protein unfolding, we quantify and interpret the strong stabilizing effect of KGlu on the ribosomal protein domain NTL9, relative to other stabilizers (KCl, KF, K2SO4) and destabilizers (GuHCl, GuHSCN). GuHSCN titrations at 20 °C, performed as a function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 36 publications
3
42
0
Order By: Relevance
“…The above results suggest that other proteins within the cytoplasm might also be stabilized by primary cytoplasmic salts, as suggested by studies of the NTL9 ribosomal protein domain . A question of particular interest, of course, is how Glu − might affect the cytoplasmic stability of proteins destined for secretion.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…The above results suggest that other proteins within the cytoplasm might also be stabilized by primary cytoplasmic salts, as suggested by studies of the NTL9 ribosomal protein domain . A question of particular interest, of course, is how Glu − might affect the cytoplasmic stability of proteins destined for secretion.…”
mentioning
confidence: 72%
“…Together, these data indicate that potassium glutamate (KGlu) is the primary cytoplasmic salt in E. coli . Furthermore, we learned that KGlu can stabilize soluble proteins, because Glu − interacts unfavorably with apolar side‐chains and amide groups . Given these facts, we examined the stability of SecA in KGlu solutions.…”
mentioning
confidence: 99%
“…However, this type of interaction is precluded in the (SSB) 65 mode since all ssDNA binding sites are occupied by DNA. We therefore suggest that high cooperativity is promoted via direct interactions between the SSB IDLs as depicted in Figure 6 and that these interactions are promoted by anions such as glutamate and acetate that are preferentially excluded from protein regions [36, 37]. Direct interactions between similar types of low complexity intrinsically disordered regions are believed to drive liquid-liquid phase separation, as exemplified by the LAF-1 protein [55].…”
Section: Discussionmentioning
confidence: 99%
“…Recent work from the Record lab [36, 37] has shown that glutamate has unfavorable interactions with and is thus preferentially excluded from all hydrocarbon groups, and carboxylate and amide oxygens, but interacts favorably with positively charged amino acids. As a result, KGlu generally promotes folding and assembly processes more than KCl.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation